META ANALISIS DAMPAK LATIHAN DRY-LAND TERHADAP PENINGKATAN PERFORMA ATLET POLO AIR - Jaka Mumara; Hamidie Ronald Daniel Ray; Boyke Mulyana (Universitas Pendidikan Indonesia, 2020)
This research was aimed at studying dry-land training on the performance of water polo athletes, starting from the dry-land training model to improving the performance of water polo athletes. The research method used was the quantitative methods with meta-analysis techniques. The research method presented an analysis of the publication of scientific journals in reputable international journals and reputable national journals relating to dry-land training on improving the performance of water polo athletes. The samples of this study were scientific articles that were published in an international journal, indexed in the highly reputable Scopus database category Q1/Q2 with H-Index, and articles that were published in an international journal with the Elsevier homepage with Impact Factors from 2014-2020. The instrument used in this study was the code submission sheet. The data analysis was conducted through SPSS version 21. The test result obtained significance values p 0.05, so that the dry land training model provided a valid effect size in improving the performance of water polo athletes. Therefore, was refused. The conclusion of this study is that the dry-land training model provides a significant effect on the performance of water polo athletes. The study also concludes that the Athlete's age, exercise intensity, and compliance with training rules become the factors that affect the improvement of water polo athlete performance.